Perilaku Profesionalisme Kepala Sekolah - Imron Rosyadi; Riza Auliya Widyaningsih; Citra Aulia Uzliva (Thawalib: Jurnal Kependidikan Islam, 2023)
The purpose of this research is to get a theory about the behavior of the principal, the professionalism of the principal, and the professional behavior of the principal. This research uses a qualitative approach with a type of literature study. Data collection techniques with documentation studies. Data processing with reduction, data presentation, and conclusion. While the data validity technique with source triangulation. The results show that: (1) The principal's behavior is an action taken based on legal stimuli at school. (2) The professionalism of the school principal is a leader who works according to the Regulation of the Minister of Education and Culture of Indonesia Number 40 of 2021, (3) The professional behavior of the school principal, first is the act of regulating learning activities in schools. Second, the action of developing school entrepreneurship. Third, the act of assessing the performance of teachers and education personnel. Fourth, the act of guiding and fostering teachers. The impact of this research can be used as a literacy reference for all school principals in Indonesia in improving and developing the quality of work in schools.